Accounting for single and aggregated forest incomes: Application to public cork oak forests in Jerez (Spain) and Iteimia (Tunisia) (Ecological Economics, 2008)
This study presents an applied improvement in the agroforestry accounting system (AAS) approach to two public cork oak forests in the Mediterranean region: Jerez (Spain) and Iteimia (Tunisia). Both forests have similar environments but differ in land property rights, labour markets and countries (developed and developing economy, respectively). The income analysis considers the differences between forest ownership, and household and landowner economic rationalities. In the case of Jerez, the public landowner has a right to exclude others from using the forest resources; community employment and natural resource conservation criteria determine Jerez's management. In the Iteimia case, the public landowner has regulated free-use rights for livestock grazing, firewood and crops so that local households can meet their needs and improve their income. Households operate by maximizing their income from the full employment of their own family workforce. The results show that Jerez's management generates negative commercial capital income for the public landowner, despite receiving significant public subsidies, while it maintains high internal forestry investment that generates additional local employment. Conversely, Iteimia produces positive commercial capital income for the public landowner and high household self-employed labour income per hectare.